2017
DOI: 10.1681/asn.2016080930
|View full text |Cite
|
Sign up to set email alerts
|

Na+/HCO3 – Cotransporter NBCn2 Mediates HCO3 − Reclamation in the Apical Membrane of Renal Proximal Tubules

Abstract: The kidney maintains systemic acid-base balance by reclaiming from the renal tubule lumen virtually all HCO filtered in glomeruli and by secreting additional H to titrate luminal buffers. For proximal tubules, which are responsible for about 80% of this activity, it is believed that HCO reclamation depends solely on H secretion, mediated by the apical Na/H exchanger NHE and the vacuolar proton pump. However, and the proton pump cannot account for all HCO reclamation. Here, we investigated the potential contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 39 publications
(92 reference statements)
3
36
0
Order By: Relevance
“…The recent discovery that the electroneutral Na/HCO 3 cotransporter NBCn2 is abundantly present in the apical membrane of the PT [90] is consistent with the idea that this transporter may mediate ~20% of total acid–base traffic across the apical membrane—previously unaccounted for. Although the mechanism of NBCn2 may be the simple cotransport of Na + plus HCO 3 − (Figure 8A), evidence that NBCn2 may in fact be an exchanger [91] is consistent with the idea that NBCn2 exchanges Na + plus CO 3 = for HCO 3 − (Figure 8B).…”
Section: Role Of Carbonic Anhydrases In Whole-body Acid–base Homeosupporting
confidence: 57%
“…The recent discovery that the electroneutral Na/HCO 3 cotransporter NBCn2 is abundantly present in the apical membrane of the PT [90] is consistent with the idea that this transporter may mediate ~20% of total acid–base traffic across the apical membrane—previously unaccounted for. Although the mechanism of NBCn2 may be the simple cotransport of Na + plus HCO 3 − (Figure 8A), evidence that NBCn2 may in fact be an exchanger [91] is consistent with the idea that NBCn2 exchanges Na + plus CO 3 = for HCO 3 − (Figure 8B).…”
Section: Role Of Carbonic Anhydrases In Whole-body Acid–base Homeosupporting
confidence: 57%
“…In mammals, the SLC4 familiy can be categorized into three major clades of HCO 3 - and/or CO 3 2- transporters including Na + -driven Cl - /HCO 3 - exchangers, electrogenic Na + coupled HCO 3 - transporters and electroneutral Na + coupled HCO 3 - transporters ( Romero et al, 2013 ; Romero et al, 2004 ). Our phylogenetic analysis based on deduced amino acid sequences suggest that SpSlc4a10 has highest identity with the mammalian clade of electroneutral Na + coupled HCO 3 - transporters, including Na + /HCO 3 - cotransporters (NBCn) and Na + -driven Cl - /HCO 3 - exchangers (NCBE) that were demonstrated to control pH i in neurons ( Wang et al, 2000 ) and enable the transcellular passage of HCO 3 - across epithelial cells of the pancreatic duct and the renal proximal tubule ( Guo et al, 2017 ; Ko et al, 2002 ). The human NBCn2 encoded by Slc4a10 has absolute requirements for Na + and HCO 3 - and appears to be a Na + -dependent Cl - /HCO 3 - exchanger that is blocked in the presence of 200 µM DIDS ( Parker et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have shown that the epithelia in the submandibular salivary gland and pancreatic duct also express NBCn1 (termed as “NBC3”) and NHEs at the apical membrane contributing to reabsorb the luminal under resting condition (Lee et al, 1998 , 2000 ; Luo et al, 2001 ; Park et al, 2002 ). In a more recent study, it is shown that the reabsorption in the proximal tubule epithelium involves the apical Na + / cotransporter NBCn2 and NHE3 (Guo et al, 2017 ). Thus, the reabsorption (and therefore luminal acidification) in these tissues involves direct -uptake via the apical NBCn1 and indirect -reabsorption dependent on proton secretion via the apical NHEs.…”
Section: Discussionmentioning
confidence: 99%